Diagnostic accuracy and reclassification potential of the acoustic CADScor algorithm in intermediate risk patients with suspected coronary artery disease. (14th October 2021) - Rasmussen, L; Winther, S; Karim, S R; Westra, J; Kheyr, M; Johansen, J K; Sondergaard, H M; Hammid, O; Nyegaard, M; Ejlersen, J A; Christiansen, E H; Eftekhari, A; et al.
Abstract: Background: Validation studies of the 2019 European Society of Cardiology pre-test probability model (ESC-PTP) for coronary artery disease (CAD) report that 35–40% of patients have intermediate pre-test risk (ESC-PTP 5-<15%). A clear strategy for deferral or referral in this group has not been established. Stratification tools with a high negative predictive value (NPV) are especially wanted to improve pre-test risk estimates. Acoustic detections of coronary stenosis are a new technology which could potentially be useful to supplement PTP stratification. One of the devices, the CADScor®System, has been shown to down-classify >40% of patients to low risk without increasing CAD prevalence. However, the clinical utility of using the CADScor algorithm (version (V)3.1) has not be validated. Purpose: 1) To validate the diagnostic performance of the CADScor®System (V3.1), and 2) to study the reclassification potential of a clinical likelihood strategy by ESC-PTP estimation supplemented by a CAD-score. Methods: In total, 1732 patients without known CAD but with symptoms suggestive hereof underwent coronary CTA as a first-line diagnostic test. Based on an interview prior to coronary CTA, the ESC-PTP model was applied and sound recordings were performed using the acoustic CADScor® System. Patients with a suspected >50% diameter stenosis in any coronary segment at coronary CTA were referred to investigation with Invasive angiography (ICA) with measurement of Fractional flow reserve (FFR). The ESC-PTP risk estimation was divided according to the recommended cut-offs of <5%, 5-<15% and >15% PTP of obstructive CAD. Haemodynamically obstructive CAD was defined as: (1) FFR value <0.80, (2) luminal diameter stenosis reduction >90%, or (3) luminal diameter stenosis reduction ≥50% if FFR was indicated but not performed. A predefined cut-off value of 20 was used for CAD-score values to rule-out CAD. Results: A suspected stenosis was found in 439 patients (26%) after coronary CTA. The follow up with ICA with FFR showed significant stenoses in 198 patients (12%). In the entire cohort using the ≤20 CAD-score cutoff for CAD rule-out, sensitivity was 85.3% (95% CI 79.5–89.9%), specificity was 40.3% (95% CI 37.8–42.9%), the PPV was 5.9% (95% CI 13.8–18.3%)), and the NPV was 95.4% (95% CI 93.4–96.9%). Hence, the disease prevalence of obstructive CAD was 4.6% in the ruled-out patients. Applying the ≤20 CAD-score cutoff for CAD rule-out in intermediate risk patients (ESC-PTP 5-<15%) a total of 316 patients (48%) were down-classified to low risk with an obstructive CAD prevalence of 3.5%. Conclusion: Having high NPV, the CADscor holds excellent rule-out power. Interestingly, the CADscor has reclassification properties in intermediate CAD risk patients where almost 50% can be deferred form further testing without increasing obstructive CAD risk. Thus, the CADscor can supplement clinical assessment to guide decisions on the need for further testing. FUNDunding Acknowledgement: Type of funding sources: Private company. Main funding source(s): The study was supported by the Health Research Fund of Central Denmark Region, Aarhus University Research foundation and by an institutional research grant from Acarix A/S, Denmark.